2011
DOI: 10.1371/journal.pone.0021945
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Acts on Sensitive Mitochondrial Proteins to Induce Death of a Fungal Pathogen Revealed by Proteomic Analysis

Abstract: How the host cells of plants and animals protect themselves against fungal invasion is a biologically interesting and economically important problem. Here we investigate the mechanistic process that leads to death of Penicillium expansum, a widespread phytopathogenic fungus, by identifying the cellular compounds affected by hydrogen peroxide (H2O2) that is frequently produced as a response of the host cells. We show that plasma membrane damage was not the main reason for H2O2-induced death of the fungal pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 68 publications
2
57
0
1
Order By: Relevance
“…The addition of H 2 O 2 to cells was reported to preferentially damage (or modify) mitochondrial proteins (Garcia et al, 2010;Perluigi et al, 2010;Qin et al, 2011;Martinez-Acedo et al, 2012;Stauch et al, 2014). In several investigations H 2 O 2 addition reduced respiratory activity and mitochondrial membrane potential.…”
Section: Redox Regulation Of the Respiratory Chainmentioning
confidence: 99%
“…The addition of H 2 O 2 to cells was reported to preferentially damage (or modify) mitochondrial proteins (Garcia et al, 2010;Perluigi et al, 2010;Qin et al, 2011;Martinez-Acedo et al, 2012;Stauch et al, 2014). In several investigations H 2 O 2 addition reduced respiratory activity and mitochondrial membrane potential.…”
Section: Redox Regulation Of the Respiratory Chainmentioning
confidence: 99%
“…Proteomic analysis of the changes of total cellular proteins in P. expansum showed that a large proportion of the differentially expressed proteins appeared to be of mitochondrial origin, implying that mitochondria may be involved in this process. Further mitochondrial sub-proteomic analysis characterized a set of mitochondrial proteins, including respiratory chain complexes I and III, F 1 F 0 ATP synthase, and mitochondrial phosphate carrier protein which might be associated with fungal death caused by H 2 O 2 (Qin et al, 2011). The pH value, as one of the most important environmental parameters, has critical influence on spore germination of P. expansum .…”
Section: Interaction Between Fruits and Fungimentioning
confidence: 99%
“…These insects are commonly present in the phenolic foams used as substrate for germination of lettuce seeds. Possible future problems can also be addressed with routine use of H 2 O 2 , since flies are horizontal transmitters of plant pathogens (El-Hamalawi, 2008) and by the fact that investigations demonstrated the antifungal action of hydrogen peroxide (Qin et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The objective of this work was to evaluate the efficiency of hydrogen peroxide (H 2 O 2 ) as a sanitizing agent (for algae control) and insecticide (for fly control) in a hydroponic commercial system. H 2 O 2 has a recognized potential for causing oxidative stress in living organisms (Vännin & Koskula, 1998;Qin et al, 2011;Wojtyla et al, 2016) and is widely used as a disinfectant and sterilant (Watt et al, 2004). The evaluation of entomopathogenic fungi to replace synthetic insecticides, in the control of fungus gnats and shore fly, was also explored as a more sustainable form of fly control (Stanghellini & El-Hamalawi, 2005) and other vector insects (Tiago et al, 2014), in a hydroponic system.…”
Section: Introductionmentioning
confidence: 99%